Microstructure and mechanical properties of hypereutectic aluminium‐silicon alloy annealing at liquid‐solid region. Issue 12 (17th December 2019) - Wang, J.; Yang, W.; Wu, C.; Tu, H.; Su, X.
Abstract: The microstructure and mechanical properties of hypereutectic Al−Si alloys containing 16 wt.%, 21 wt.% and 30 wt.% Si (AlSi16, AlSi21 and AlSi30) have been investigated in "as‐cast" and "annealed at the liquid‐solid region". The results show that the morphologies of primary Silicon in AlSi30 changed hardly after being annealed at 587 °C for different time. The morphology of eutectic silicon in all Al−Si alloys changed from flake‐like to granular after being annealed at 587 °C for 5 min to 15 min. With the increase of silicon content, the average size of the granular eutectic silicon decreased. The spheroidized effect for the eutectic silicon in AlSi21 was the best. After being annealed for 15 min, the tensile strength of AlSi16, AlSi21 and AlSi30 alloys decreased by 10.4 %, 11.7 % and 11.5 %, respectively. Their elongation increased 61.1 %, 50.0 % and 33.3 %, respectively. The comprehensive mechanical properties of AlSi16 and AlSi21 alloys were improved markedly after being annealed at 587 °C for 15 min.